Kinetic modelling of combustion in a spark ignition engine with water injection. (1st January 2021) - Yuan, Hao; Giles, Karl; Zhu, Sipeng; Howson, Simeon; Lewis, Andrew; Akehurst, Sam; Turner, Niall; Harris, James; Fowler, Gavin; Geddes, John
Highlights: Combustion phasing with and without water is similar under knock limited conditions. Charge cooling is more significant than dilution in advancing combustion phasing. NO chemistry is critical for the initial heat release in the unburned gas zone. Water has a negligible chemical impact on the autoignitioin except acting as a collision partner. Water injection decreases the NO formation due to its cooling effects on the flame. Abstract: This work models the impact of direct water injection on the combustion process in a spark ignition engine. It uses a two-zone kinetic model coupled with detailed combustion chemistry to highlight the thermodynamic and chemical-kinetic interactions between gasoline combustion and water injection. The modelling results agree closely with measurements from a highly boosted, direct injection gasoline engine. This study first proposes an approach to model the mass fraction burned (MFB) profile using a representative in-cylinder pressure trace. The derived MFB profile is then used as the input for a two-zone kinetic model. Within this model, predictive kinetic modelling is used to estimate the knock limited spark advance (KLSA) for a baseline engine operating condition without water injection and subsequently, for several conditions with water injection. Predicted KLSA values obtained using this method agree closely with measured results. Utilising the approach developed in this study, the modelled MFB profile at the baseline operating condition was found to be similar to that obtained at the condition with a water/fuel ratio (WFR) of 60%. This result is likely due to the competing and contrasting effects of reduced in-cylinder temperature versus more advanced combustion phasing at conditions with water injection. Further thermodynamic analysis shows that the charge cooling effect afforded by direct water injection is much greater than the dilution effect in terms of advancing the knock limited combustion phasing. Water injection also affects the kinetic processes that take place in the unburned gas zone, but mainly by altering the in-cylinder thermodynamic conditions – the injected water is not directly involved in the low temperature chemistry in the unburned gas zone, it simply acts as a collision partner.